Analysis of the Influence of Agents' Credibility Through Digital Media and Digital Promotions on Purchase Decisions Toward Insurance Products - Sudirjo, Frans; Adhi Pramono, Susatyo; Arief, Ilham; Nana Hermana, Asep; Sulistya Kusuma Wardhani, Annisa Risqi (Jurnal Informasi dan Teknologi, 2024)
This research aims to see the influence of interpersonal communication by insurance agents on customers' decisions to purchase products and whether the agent's credibility impacts customers' purchasing decisions regarding insurance service products. This type of research is quantitative. Data collection using questionnaires. The method used in taking this sample was simple random sampling. The sample in this study was 100. The data analysis technique used was multiple regression analysis. The analysis found that interpersonal communication and the credibility of insurance agents significantly influence customers' purchasing decisions when purchasing insurance service products. The study's results also show that the hypothesis proposed in this research has been proven: interpersonal communication and insurance agent credibility significantly influence customer purchasing decisions. Thus, insurance companies need to pay attention to and improve interpersonal communication strategies and strengthen the credibility of insurance agents to enhance customer purchasing decisions and their sales performance.